2005
DOI: 10.1590/s0004-27302005000400010
|View full text |Cite
|
Sign up to set email alerts
|

Proporções corporais em um grupo de pacientes brasileiras com Síndrome de Turner

Abstract: RESUMOObjetivo: Trata-se do primeiro estudo brasileiro com o objetivo de avaliar as proporções corporais de pacientes com síndrome de Turner (ST) não tratadas com hormônio de crescimento. Métodos: Estudo transversal de 50 pacientes com ST (5 a 43 anos), avaliando-se idade, cariótipo, desenvolvimento puberal e medidas de estatura em pé e sentada, envergadura, peso, IMC, perímetro cefálico, mão e pé, perna, relação entre cintura e quadril, diâmetros biacromial e bi-ilíaco. Transformação dos dados em escore z de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…While these parameters have been previously assessed in other studies, the currrent analysis was performed in a well-defined population of TS women (≥20 years old) and the results were compared to that of a sex-, age- and BMI-matched reference group. In concordance with previous studies,3,4,22,23 our TS subjects not only presented with altered anthropometry, but also with altered body composition.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While these parameters have been previously assessed in other studies, the currrent analysis was performed in a well-defined population of TS women (≥20 years old) and the results were compared to that of a sex-, age- and BMI-matched reference group. In concordance with previous studies,3,4,22,23 our TS subjects not only presented with altered anthropometry, but also with altered body composition.…”
Section: Discussionsupporting
confidence: 93%
“…This disorder is one the most common human chromosomal abnormalities, occurring in approximately 1:2500 live female births 2. Patients with TS generally have severely deficient body height and distorted body proportions when compared with healthy women 36. Congenital cardiovascular disease affects 30% of patients with TS and the risk of premature death by this condition is increased 20-fold in TS subjects 7.…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed a standard deviation of -3.28 ± 1.0 for the leg-length segment 15 . Recent studies have found similar results, in which leg length growth was reduced by -2.69 to -3.69 SD on average 16 . The literature notes the deficit of insulin-like growth factor 1 (IGF-1), which is primarily responsible for the actions of the growth hormone (GH), as one of the factors that influences the reduced growth of individuals with DS.…”
Section: Discussionsupporting
confidence: 65%
“…The anthropometric data from the other patients were obtained by reviewing patients' files. Some of the patients with ISS, TS and SHOX defects have been previously reported [8,13]. Height was measured with a calibrated stadiometer to the nearest 0.1 cm, with the subjects barefooted.…”
Section: Methodsmentioning
confidence: 99%
“…In females with Turner syndrome (TS), the partial or complete X chromosome monosomy leads to SHOX haploinsufficiency which partially explains the short stature and some skeletal features observed in these patients such as skeletal disproportions, micrognathia, cubitus valgus, high-arched palate, short 4th metacarpals, genu valgum, scoliosis and Madelung wrist deformity [3,4]. Abnormal body disproportions were observed in a substantial percentage of females with TS [5,6,7,8]. …”
Section: Introductionmentioning
confidence: 99%